Paracoccidioides brasiliensis (Lutz, 1908) isolado por meio de hemocultura em um paciente portadora de símdrome de imunodeficiência adquirida (SIDA) - Hadad, D. J.; Pires, M. D.; Petry, T. C.; Orozco, SFB; Melhem, MDSC; Paes, RAC; Mendes-Giannini, Maria José Soares [UNESP] (Inst Medicina Tropical, 1992)
A case of an AIDS-patient with positive blood culture for Paracoccidioides brasiliensis is reported. The patient was a 29 years old male born in Nova Londrina (Parana State, Brazil) who presented splenomegaly and fever of unknown origin. Three blood cultures were performed, each one of them for aerobic bacteria, mycobacteria and fungi. Cultures for aerobic bacteria and mycobacteria were negative. However, the yeast phase P. brasiliensis was isolated from two cultures in BHI agar, 20 days after inoculation in Negroni medium. The patient was classified in group V according to the Centers for Disease Control (CDC) criteria for AIDS, due to a Pneumocystis carinii pneumonia. Treatment was discontinued due to an individual decision of the patient on the second dose of amphotericin B. This antibiotic was replaced by ketoconazole in the daily dose of 800 mg. The patient died one year after the isolation of P. brasiliensis on blood culture.
Paracoccidioides-brasiliensis isolated by hemoculture from a patient with AIDS